Estimating Customer Potential Value using panel data of a Spanish bank - Estrella-Ramón, Antonia; Sánchez-Pérez, Manuel; Swinnen, Gilbert; Vanhoof, Koen (Journal of Business Economics and Management, 2016)
The main goal of this paper is the calculation of a multi-product model of Customer Potential Value using the Probit method. The results of this first analysis are used to perform an ex-post segmentation of customers, whose output can be employed to improve Customer Relationship Management strategies of the companies. Our research contributes to the consumer behaviour literature insofar as, according to our knowledge, no previous work has examined collectively the proposed drivers of Customer Potential Value in a multi-services retailer. To achieve these objectives, we use a panel data of a Spanish bank. The results allow us to confirm the influence of a set of behavioural variables on the ownership of different banking products and identify those customers whose value is higher and lower through the calculation of Customer Potential Value.